2010
DOI: 10.1901/jaba.2010.43-473
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Preference for Items During Periods of Extended Access Based on Early Response Allocation

Abstract: Top-ranked items were identified during 30-min free-operant preference assessments for 9 individuals. Data from each session were analyzed to identify the item (a) that was engaged with first in each session and (b) to which the most responding was allocated after 5 min, 10 min, 15 min, 20 min, and 25 min had elapsed in each session. The results indicated that the first-engaged item and the 5-min high-allocation item predicted the top-ranked item in 55% and 62% of the sessions, respectively. The results also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…NS = not selected Identifying the minimum amount of time necessary to empirically determine reinforcers would be highly valuable in future research as well. FO assessments are typically conducted in 5-min or longer durations (Roane et al, 1998;Rapp, Rojas, Colby-Dirksen, Swanson, & Marvin, 2010); however, this study used 2-min assessment sessions, which produced similar results as the PS and MSWO assessments. Thus, it is possible that FO assessments can be potentially more efficient than those reported previously.…”
Section: Resultsmentioning
confidence: 97%
“…NS = not selected Identifying the minimum amount of time necessary to empirically determine reinforcers would be highly valuable in future research as well. FO assessments are typically conducted in 5-min or longer durations (Roane et al, 1998;Rapp, Rojas, Colby-Dirksen, Swanson, & Marvin, 2010); however, this study used 2-min assessment sessions, which produced similar results as the PS and MSWO assessments. Thus, it is possible that FO assessments can be potentially more efficient than those reported previously.…”
Section: Resultsmentioning
confidence: 97%
“…Relatedly, one potential limitation to the FOCSA model is that it requires the participant to manipulate two or more items across the assessment sessions. Without distributed response allocation, the analysis is similar to a brief free-operant stimulus preference assessment for which the limitations of exclusive allocation to a single, highly preferred item have been previously noted (e.g., Rapp, Rojas, Colby-Dirksen, Swanson, & Marvin, 2010; Roane et al, 1998). We addressed this problem by (a) conducting additional sessions with all the items and (b) removing the highly preferred item and conducting additional sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Several applied studies that have examined differences in preference assessment outcomes as a function of duration of stimulus availability or engagement may lend some support for the notion that continuity of access may play an important role in determining the reinforcing value of some stimuli. In general, results of this research have suggested that relative preference for stimuli may differ according to duration of access (e.g., Kodak, Fisher, Kelley, & Kisamore, ; Steinhilber & Johnson, ) or that preference based on engagement during short durations of access may not always predict preference based on responding during extended periods of access (Rapp, Rojas, Colby‐Dirksen, Swanson, & Marvin, ). For example, Steinhilber and Johnson () compared preference for and reinforcing efficacy of various activities (e.g., music, video games) using a multiple‐stimulus‐without‐replacement (MWSO) preference assessment (DeLeon & Iwata, ) when the selected stimuli were delivered for 15 s or 15 min.…”
mentioning
confidence: 89%